Computational instability analysis of inflated hyperelastic thin shells using subdivision surfaces - Liu, Zhaowei; McBride, Andrew; Ghosh, Abhishek; Heltai, Luca; Huang, Weicheng; Yu, Tiantang; Steinmann, Paul; Saxena, Prashant (Computational Mechanics, 2024)
The inflation of hyperelastic thin shells is a highly nonlinear problem that arises in multiple important engineering applications. It is characterised by severe kinematic and constitutive nonlinearities and is subject to various forms of instabilities. To accurately simulate this challenging problem, we present an isogeometric approach to compute the inflation and associated large deformation of hyperelastic thin shells following the Kirchhoff–Love hypothesis. Both the geometry and the deformation field are discretized using Catmull–Clark subdivision bases which provide the required C1-continuous finite element approximation. To follow the complex nonlinear response exhibited by hyperelastic thin shells, inflation is simulated incrementally, and each incremental step is solved using the Newton–Raphson method enriched with arc-length control. An eigenvalue analysis of the linear system after each incremental step assesses the possibility of bifurcation to a lower energy mode upon loss of stability. The proposed method is first validated using benchmark problems and then applied to engineering applications, where the ability to simulate large deformation and associated complex instabilities is clearly demonstrated.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Catmull–Clark subdivision surfaces; Hyperelastic shells; Isogeometric analysis; Shell buckling; Stability analysis